Shift of parameter replacing every occurrence of t

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (β ) − sin(α) sin(β )) Since i2 = −1 + i (sin(α) cos(β ) + cos(α) sin(β )) Factor out i = cos(α + β ) + i sin(α + β ) Sum identities = cis(α + β ) Definition of ‘cis’ Putting this together with our earlier work, we get zw = |z ||w|cis(α + β ), as required. Moving right along, we next take aim at the Power Rule, better known as DeMoivre’s Theorem.11 We proceed by induction on n. Let P (n) be the sentence z n = |z |n cis(nθ). Then P (1) is true, since z 1 = z = |z |cis(θ) = |z |1 cis(1 · θ). We now assume P (k ) is true, that is, we assume z k = |z |k cis(kθ) for some k ≥ 1. Our goal is to show that P (k + 1) is true, or that z k+1 = |z |k+1 cis((k + 1)θ). We have z k+1 = z k z Properties of Exponents = |z |k cis(kθ) = |z |k |z | = 11 (|z |cis(θ)) Induction Hypothesis cis(kθ + θ) |z |k+1 cis((k Product Rule + 1)θ) Compare this proof with the proof of the Power Rule in Theorem 11.14. 11.7 Polar Form of Complex Numbers 849 Hence, assuming P (k ) is true, we have that P (k + 1) is true, so by the...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online